Atividade antimicrobiana de cimentos obturadores endodônticos biocerâmicos frente a enterococcus faecalis em biofilme : estudo in vitro - Viana, Francisca Lívia Parente (2019)
The aim of this study was to evaluate, in vitro, the antimicrobial activity of three bioceramic endodontic sealers against biofilms of two Enterococcus faecalis strains (ATCC 29212 and ATCC 4083), comparing them to a resin sealer. BioRoot RCS, Bio-C Sealer and Sealer Plus BC bioceramic sealers and an epoxy-amine resin (AH Plus) sealer, used as standard, were evaluated. Antimicrobial activity tests were performed by direct and indirect contact. For the direct contact test the fresh sealers were applied to nitrocellulose membranes (pores 0.22 μm in size and 13 mm in diameter) with E. faecalis biofilms grown for 48 hours. For the indirect contact test, sterile nitrocellulose membranes were interposed between the sealer and the membranes with the grown biofilms. The contact time in both conditions was 30 minutes. In all the tests a control group was prepared, in which the biofilm was not exposed to any material. After the time of contact the sealers were removed and the membranes with the biofilms transferred to a flask with sterile saline solution. A series of dilutions was performed and the bacterial survival was determined by the bacterial culture of each dilution using a plate with BHI agar. The colony forming units were counted after incubation for 24 hours at 37 ° C. All assays were performed in triplicate on three different occasions. For statistical analysis, the Kruskal-Wallis and Student-Newman-Keuls tests were used, both with a significance of 5.0%. The results showed an antimicrobial activity of Bio-C Sealer, Sealer Plus BC and BioRoot RCS sealers, when in direct contact conditions, which were statistically different from the control group (P <0.05). In the condition of indirect contact only Sealer Plus BC and AH Plus showed significant difference from the control group (P <0.05). Considering of the above, and the conditions of the study, it was concluded that the bioceramic sealers presented antimicrobial action against bacterial biofilms of the two strains of E. faecalis tested when in direct contact condition, however, only sealer Sealer Plus BC was effective when in indirect contact.